Strategic Management in Empowering Economic Independence of Islamic Boarding Schools - Moch. Rusli (Journal of Islamic Studies and Education, 2023)
An Islamic boarding school, known as "Pondok Pesantren," serves as an institution for religious education and a place for practical engagement in social, artistic, and economic activities. These schools have the potential for economic development and the realization of economic self-reliance through their cooperative units, referred to as "Koperasi Pondok Pesantren." However, many Pesantren have yet to fully harness their potential due to a lack of knowledge in strategic management. Strategic management can be implemented under the guidance of leadership to achieve the institution's vision and mission. Riyadlotut Thalabah Islamic Boarding School is one such Pesantren that possesses a cooperative unit (Kopontren). This research aims to assess the extent to which strategic management and stakeholder theory are applied in this context. Through a qualitative descriptive analysis method, which includes interviews and primary reports, the study has revealed several factors that influence the economic self-reliance of the Pesantren. The findings indicate that the planning function is the most influential aspect in achieving economic self-reliance for the Pesantren. Additionally, strong leadership from the school's administrators, teachers (ustadz/ustadzah), students (santri), stakeholders, an effective information system, and a viable market are all crucial factors in realizing the economic self-reliance of Riyadlotut Thalabah Islamic Boarding School in the economic field.